Challenges and Prospects of Implementation of Teaching of English to Speakers of Other Languages (TESOL) Approaches in Nigeria - Olajoke, Akinkurolere Susan; Olamide, Ijadimine (American Journal of Education and Learning, 2017)
This paper looks into the challenges and prospects of implementing teaching of English to speakers of other languages(TESOL) approaches in Nigeria against the background of the Nigerian National Policy on Education (2004) which legitimise the teaching of English as a the official language. The review paper is a shift from the usual approach of examining the teaching of English as a Second Language(TESL) to teaching of English to Speakers of other Languages(TESOL).The two approaches recognize previous knowledge of English language but TESOL has a wider conceptual view. However, challenges of TESOL are highlighted in order to call the attention of stakeholders. The challenges of TESOL require urgent attention as previous studies have dwelt much on prospects which are interrelated with functions of English and importance of teaching English as a Second Language.